2019
DOI: 10.3390/ijms20112791
|View full text |Cite
|
Sign up to set email alerts
|

Repression of TERRA Expression by Subtelomeric DNA Methylation Is Dependent on NRF1 Binding

Abstract: Chromosome ends are transcribed into long noncoding telomeric repeat-containing RNA (TERRA) from subtelomeric promoters. A class of TERRA promoters are associated with CpG islands embedded in repetitive DNA tracts. Cytosines in these subtelomeric CpG islands are frequently methylated in telomerase-positive cancer cells, and demethylation induced by depletion of DNA methyltransferases is associated with increased TERRA levels. However, the direct evidence and the underlying mechanism regulating TERRA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
7
1
Order By: Relevance
“…While both telomeric and non-telomeric TAR sequences are enriched for CTCF, the non-telomeric TAR sequences are more enriched for activating chromatin marks H3K27ac and H3K4me3, suggesting differences in TERRA activity (Fig 1f). Previous studies have focused on the roles and regulation of TAR in the subtelomere (27)(28)(29), however our results indicate biological functionality of TAR sequences outside the subtelomere as well. Overall, using only publically available short-read data with the new T2T-CHM13 reference and dynamic k-mer assisted mapping, we uncovered novel regulatory features in centromeric, pericentromeric, and subtelomeric repeats and display the usage of this technique for investigating disease related epigenetic dysregulation.…”
Section: Introductioncontrasting
confidence: 53%
“…While both telomeric and non-telomeric TAR sequences are enriched for CTCF, the non-telomeric TAR sequences are more enriched for activating chromatin marks H3K27ac and H3K4me3, suggesting differences in TERRA activity (Fig 1f). Previous studies have focused on the roles and regulation of TAR in the subtelomere (27)(28)(29), however our results indicate biological functionality of TAR sequences outside the subtelomere as well. Overall, using only publically available short-read data with the new T2T-CHM13 reference and dynamic k-mer assisted mapping, we uncovered novel regulatory features in centromeric, pericentromeric, and subtelomeric repeats and display the usage of this technique for investigating disease related epigenetic dysregulation.…”
Section: Introductioncontrasting
confidence: 53%
“…Impaired de novo methylation during embryogenesis leads to devastating effects in ICF1 patients who are characterized by short telomeres and high TERRA levels. Interestingly a recent study showed that loss of methylation in the subtelomeric CpG islands in HeLa led to an NRF1-dependent up-regulation of TERRA expression strengthening the link between CpG-island containing promoters and TERRA transcription (Le Berre et al 2019). We established that the length of telomeres in DNA methyltransferase deficient DKO cells is shorter at chromosome ends independently of their individual TERRA expression levels.…”
Section: Discussionmentioning
confidence: 73%
“…1B-D). The intensity of TERRA-FISH foci, however, does not reflect the total levels of UUAGGG repeats in human cells, as shown by slot-blot hybridization of total RNA isolated from HCA2 normal fibroblasts and LB37 lung cancer cells which, because of subtelomeric promoter hypomethylation (Nergadze et al 2009;Diman et al 2016;Sagie et al 2017;Feretzaki et al 2019;Le Berre et al 2019), strongly up-regulate telomeric transcription (Fig. 1E,F).…”
Section: Terra-fish Foci Colocalize With Telomeres and Their Intensit...mentioning
confidence: 96%